Comparing thermal stimulation techniques in infrared thermographic inspection of corrosion in steel; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Chulkov A. O. Arseniy Olegovich (2015, 2015)
Title screen